A new species of Passiflora (subgenus Passiflora, Passifloraceae) from Bahia, Brazil. Issue 1 (19th November 2019) - Imig, Daniela Cristina; Amano, Érika
Abstract : A new species of Passiflora subgenus Passiflora from the Brazilian flora is described and illustrated in this article. Passiflora faleiroi was collected in Prado, state of Bahia, and belongs to the supersection Stipulata, section Granadillastrum . Passiflora faleiroi is compared to two similar species, P. mucronata Lam. and P. silvestris Vell.